APLIKASI MOBILE MONITORING KEHADIRAN SISWA MENGGUNAKAN TEKNOLOGI QUICK RESPONSE - Misrawati Aprilyana Puspa; Jorry Karim; Marlin Lasena; Zufrianto Dunggio (JSAI (Journal Scientific and Applied Informatics), 2023)
Attendance is an important part of every educational institution. Where attendance is one of the main supports that can support and motivate every activity carried out in it. Schools are educational institutions designed for student instruction under the supervision of teachers. Most countries have a formal education system, which is generally mandatory, as well as attendance at SMK Negeri 5 Gorontalo which still uses a manual method (signature), this method is very vulnerable for an educational institution because the level of discipline that cannot be controlled and can be misused by irresponsible people, another disadvantage that may arise in the manual attendance system is data recapitulation which still takes a lot of time and effort. Another disadvantage, parents of students cannot find out about their son's attendance at school so it is considered less effective and efficient. For this reason, the purpose of this research is to create and design an information system for monitoring student attendance using an android-based QR Code at SMK 5 Gorontalo so that it can make it easier for parents to monitor attendance. This application is designed using java programming language software, namely Android Studio, for PHP programming language using Dreamwever software, and for data storage using Mysql, as well as a tool for modeling using UML (Unified Modeling Language).